Assessing the variability and discriminatory power of elemental fingerprints in whiteleg shrimp Litopenaeus vannamei from major shrimp production countries. (March 2022) - Davis, Robert P.; Boyd, Claude E.; Godumala, Ravibabu; Ch Mohan, Avanigadda B.; Gonzalez, Arturo; Duy, Nguyen Phuong; Sasmita J, Pande Gde; Ahyani, Nur; Shatova, Olga; Wakefield, Joshua; Harris, Blake; McNevin, Aaron A.; et al.
Abstract: Provenance of seafood items is a concern for consumers and importers alike. Elemental profiling has been put forth as a potential tool to improve seafood traceability. Whiteleg shrimp Litopenaeus vannamei collected from farms in Ecuador, India, Indonesia, Vietnam, and Thailand were classified to country of origin based on element concentrations in muscle tissue. Shrimp were dried, digested, and analyzed via ICP-MS. Out of the 41 elements investigated, 33 are reported as being above detection limits. Twenty-eight elements were statistically different across countries, and of these 28, Ecuador had unique group membership in 7. A random forest classification model utilizing 16 elements had an overall accuracy of 91% of correctly classified samples to country of origin. A canonical discriminant analysis was conducted to understand the variation in the data and identify elements that were important to differentiation in multi-dimension space. Elements identified as important contributors were Al, As, B, Ca, Co, Cs, Sr, and V. This study shows that shrimp from Ecuador tend to be more mineralized than shrimp from Asia, and classification models can discern samples from these countries successfully. This demonstrates the potential of a traceability database for cultured shrimp products from predominant production countries. Highlights: Shrimp from 5 countries were collected from farms for elemental analysis. Trace elements classified shrimp in discriminant analysis with 91% accuracy. Ecuadorian shrimp have a unique profile compared to Asian shrimp. This study provides further evidence for elemental profiling as a traceability tool.